Psychological prediction of injury in elite swimmers - Bond, J. W.; Miller, B. P.; Chrisfield, P. M. (International Journal of Sports Medicine, 1988)
Previous research has suggested that psychological factors related to attention and anxiety may identify the injury-prone athlete. This investigation used elite swimmers (N = 33) over a 12-month period. Psychological variables were measured using Nideffer's Test of Attentional Style (TAIS). 56% of the injuries were gradual in onset and resulted from training overuse. Although these and other intrinsic injuries might theoretically be lower in those with effective internal attentional styles, this supposition was not supported. Actually, the results supported the converse. Swimmers with more effective attentional profiles sustained more injuries. The TAIS was not shown to be useful for predicting injuries. The sensitivity of the TAIS to assess appropriate attentional profiles in swimmers was questioned.